2005
DOI: 10.1542/peds.2004-0542
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Unique, Nurse-Inserted, Peripherally Inserted Central Catheter Program

Abstract: This novel, pediatric nurse-inserted PICC program has a good safety profile, high success rate, and low postprocedural complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 7 publications
3
29
0
13
Order By: Relevance
“…Peripherally Inserted Central Catheter (PICC) have been used in neonates for more than 20 years, as well as in children undergoing chemotherapy [16][17][18][19] or treatment for infectious diseases [20]. It has been shown in such populations that PICCs are more stable than short peripheral cannulae and need less frequent replacement [7,9,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripherally Inserted Central Catheter (PICC) have been used in neonates for more than 20 years, as well as in children undergoing chemotherapy [16][17][18][19] or treatment for infectious diseases [20]. It has been shown in such populations that PICCs are more stable than short peripheral cannulae and need less frequent replacement [7,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in such populations that PICCs are more stable than short peripheral cannulae and need less frequent replacement [7,9,16]. Their use has resulted in greater comfort in young patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…That incidence of malposition is similar to the incidences reported in other studies. 32,38,39 Malpositioned tips were located in the upper or middle third of the SVC, the ipsilateral subclavian vein, the right atrium, the ipsilateral internal jugular vein, and the axillary vein. In 1 case, the tip was coiled in the SVC (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The tip locations and incidences are similar to those reported in other studies. 32,38,39 These reports show that about 58% of malpositions were corrected with catheter exchange, and 83% were corrected by repositioning the catheter in the interventional radiology division under imaging guidance. 32,38,39 In this study, we demonstrated a modification of PICC insertion: taking the chest radiograph earlier, which makes it easier to correct malpositions at the bedside, with high success rates and without catheter exchange.…”
Section: Discussionmentioning
confidence: 99%
“…28 Bedside PICC placement can also present additional challenges related to limited workspace, suboptimal access to patients, infection control, and lack of access to additional equipment, if needed. [29][30][31][32] Before the start of the PICC team centralization, an effective decision-making process to determine the appropriate location for PICC insertion had not been established, resulting in a large number of unnecessary bedside placements. Because we believed this was not the safest option for all patients, 28 we investigated the reasons why bedside PICC insertions were requested.…”
Section: Locationmentioning
confidence: 99%